Applications of photodynamic therapy in keratitis - Ayaz, Anwar *; Khan, Naveed Ahmed; Alharbi, Ahmad M; Alhazmi, Ayman; Siddiqui, Ruqaiyyah (Springer, 2024)
Keratitis is corneal inflammatory disease which may be caused by several reason such as an injury, allergy, as well as a microbial infection. Besides these, overexposure to ultraviolet light and unhygienic practice of contact lenses are also associated with keratitis. Based on the cause of keratitis, different lines of treatments are recommended. Photodynamic therapy is a promising approach that utilizes light activated compounds to instigate either killing or healing mechanism to treat various diseases including both communicable and non-communicable diseases. This review focuses on clinically-important patent applications and the recent literature for the use of photodynamic therapy against keratitis.